AMELIORATIVE MEASURE FOR COLD IN BLACK BENGAL GOATS IN COASTAL ODISHA CLIMATE (Indian Journal of Animal Production and Management, 2016)
The objective of the study was to evaluate the effect of slatted floor in ameliorating the effects of cold  stress in Black Bengal goats in Odisha. Different vital physiological signs, serum biochemical parameters,  stress hormone like cortisol and browsing behaviour were studied to assess the level of stress in the two  flooring pattern. Serum haptoglobin and cortisol were assayed as stress indicators in goats. Twenty adult  Black Bengal goats (more than 6 months of age) were randomly selected from the Instructional Livestock  Farm, OUAT and distributed into two groups (10 in each group) so that th.e mean body weight in both the  groups were statistically equivalent. Statistically significant variation (P
Keywords: Cold stress; Cortisol; Haptoglobin; Pulse rate; Slatted floor